A Randomized Double‐Blind, Placebo‐Controlled, Cross‐Over Study Using Baclofen in the Treatment of Rumination Syndrome. (January 2018) - Pauwels, Ans; Broers, Charlotte; Van Houtte, Brecht; Rommel, Nathalie; Vanuytsel, Tim; Tack, Jan
Abstract : OBJECTIVES: Both rumination syndrome and supra‐gastric belching (SGB) have limited treatment options. We demonstrated (open‐label) that baclofen reduces pressure flow events in these patients. We aimed to study the effect of baclofen in a placebo‐controlled, double‐blind, cross‐over study in patients with clinically suspected rumination and/or SGB. METHODS: Twenty tertiary‐care patients (mean age 42 years (range 18–61), 13f) with clinically suspected rumination and/or SGB were randomized to receive baclofen (10 mg, t.i.d) or placebo for 2 weeks with cross‐over to the alternative intervention after a 1 week wash‐out period. At the end of each treatment period, patients underwent a solid‐state high‐resolution impedance manometry measurement, during which they registered symptoms. Patients received a solid meal and recordings continued for 1 h. They scored overall treatment evaluation (OTE) on a −3 to +3 scale. RESULTS: Both the number of regurgitation event markers and rumination episodes were significantly decreased after baclofen (6 (0–19) vs. 4 (0–14), P =0.04; 13 (8–22) vs. 8 (3–11), P =0.004). The number of SGB episodes was similar in both groups. Lower esophageal sphincter (LES) pressure was significantly higher and the number of transient LES relaxations was significantly lower after baclofen (17.8 (12.7–22.7) vs. 13.1 (7.2–16.9) mm Hg, P =0.0002; 4(1–8) vs. 7(3–12), P =0.17). The number of reflux events decreased in the baclofen condition (4 (1–9) vs. 3 (0–6), P =0.03). Straining episodes were similar in both arms, but the rumination/straining ratio was significantly lower in the baclofen arm (0.06 (0–0.32) vs. 0.33 (0–0.51), P =0.0012). OTE was superior after baclofen compared to placebo ( P =0.03). CONCLUSIONS: Baclofen is an effective treatment option for patients with rumination syndrome, probably through its effect on LES pressure.